Design and Development of Machine Learning Technique for Software Project Risk Assessment - A Review - Mahdi M.N.; M.h M.Z.; Yusof A.; Cheng L.K.; Mohd Azmi M.S.; Ahmad A.R. (Institute of Electrical and Electronics Engineers Inc., 2023)
Machine learning; Project management; Software design; Design and Development; Development performance; Literature reviews; Machine learning approaches; Machine learning techniques; Size metrics; Software project; Software project risks; Risk assessment